Ознаки суб’єкта злочинів проти порядку несення та проходження військової служби - Касько, Тетяна Юріївна; Касько, Татьяна Юрьевна; Kas'ko, Tat'jana (Одеса : Юрид. л-ра, 2014)
The article is dedicated to the establishment of the characteristics of the subject of crimes against the bearing and passage of military service (military crimes). The problematic question of criminal responsibility for said crimes of persons that are unlawfully accepted (enlisted), passing to military service is highlighted.
Касько Т. Ю. Ознаки суб’єкта злочинів проти порядку несення та проходження військової служби / Т. Ю. Касько // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 412-418.
Keywords: злочини проти порядку несення та проходження військової служби; військові злочини; суб’єкт злочину; Розділ ХІХ Кримінального кодексу України; преступления против порядка несения и прохождения военной службы; военные преступления; субъект преступления; Раздел XIX Уголовного кодекса Украины; crimes against the order of bearing and passage of military service; military crimes; subject of crime; Chapter XIX Criminal Code Ukraine